DEVELOPING APPRECIATION TO MULTICULTURAL TYPICALITY BY INTRODUCING TRADITIONAL SPORT OF LANGGA MARTIAL ART ROOTED FROM GORONTALO CULTURE (LANGGA MARTIAL ART INTEGRATED TO THE PESH TEACHING AND LEARNING IN JHS/IJHS OF GORONTALO CITY) - Hadjarati, Hartono; Hidayah, Taufiq (The Journal of Educational Development, 2016)
The content of local wisdom in 2013 Curriculum is expected to develop appreciation to multicultural typicality by introducing traditional games and sport rooted from the culture of Indonesian ethic groups. A martial art is expression by which people defend themselves and has deep philosophical teaching to be mastered by individuals who want to learn self-defense. Because the martial art has developed into an achievement sport, the philosophical values are fading and are replaced by the pursuance of winning or losing. This study is meant (1) to introduce Langga as the local content integrated into self-defense activities within the PESH teaching and learning, (2) to develop appreciation to multicultural typicality by introducing Langga martial art rooted from Gorontalo culture. This is a qualitative study and the data were collected by using observation, documents and intertviews, and analyzed by using an interactive flow model. Langga martial art is not only designed to develop skills and knowledge, but also intended to provide the students with understanding about physical movement in sport, to generate the historical motivation to inherit the culture and historical values of the ancestors as national cultural wealth coming from Gorontalo, and to encourage students to understand and conserve the local culture.